Immunoglobulin M antibodies to aquaporin-4 in neuromyelitis optica and related disorders - Jarius, Sven; Franciotta, Diego; Bergamaschi, Roberto; Wildemann, Brigitte; Wandinger, Klaus-Peter (Clinical chemistry and laboratory medicine, 2010)
Background: Neuromyelitis optica (NMO, Devic syndrome) is an inflammatory disorder of the central nervous system of putative autoimmune etiology that primarily affects the optic nerves and spinal cord. NMO is frequently associated with immunoglobulin G (IgG) antibodies to aquaporin-4 (AQP4-IgG), which are thought to be involved in the patho-genesis of the disease. The frequency and diagnostic relevance of immunoglobulin M (IgM) antibodies to aquaporin-4 (AQP4-IgM) in patients with NMO is essentially not known. Testing for AQP4-IgM may be of importance since 20%-30% of patients with NMO are negative for AQP4-IgG. Moreover, IgM antibodies are more potent activators of complement compared with IgG, and are detectable at NMO lesional sites. Methods: Serum samples from 42 patients with NMO spectrum disorders (NMOSD) and from 66 controls were tested for IgM AQP4-Ab using a cell-based assay employing HEK293 cells transfected with human full length AQP4. To control for possible interactions between IgG and IgM, serum was depleted of IgG prior to testing by indirect immunofluorescence. Results: IgM AQP4-Ab were detectable in 4/42 samples from patients with NMOSD, but in none of the 66 control samples. In three patients, titers were higher following depletion of total IgG from the samples. One sample was positive only after precipitation of total IgG. Conclusions: AQP4 antibodies of the IgM class exist in almost 10% of patients with NMO and might contribute to lesion pathology. Routine testing for AQP4-IgM appears to not be justified, as all AQP4-IgM positive patients were also positive for AQP4-IgG, and none of the AQP4-IgG negative samples were positive for AQP4-IgM. Clin Chem Lab Med 2010;48:659-63.
Gesehen am 26.07.2023